Tending a Wild Garden: Library Web Design for Persons with Disabilities - Vandenbark, R. Todd (Information Technology and Libraries, 2010)
Nearly one-fifth of Americans have some form of disability, and accessibility guidelines and standards that apply to libraries are complicated, unclear, and difficult to achieve. Understanding how persons with disabilities access Web-based content is critical to accessible design. Recent research supports the use of a database-driven model for library Web development. Existing technologies offer a variety of tools to meet disabled patrons’ needs, and resources exist to assist library professionals in obtaining and evaluating product accessibility information from vendors. Librarians in charge of technology can best serve these patrons by proactively updating and adapting services as assistive technologies improve.